Autoradiographic labelling of 5-HT3 receptors in the hemi-parkinsonian rat brain. (April 2022) - Kwan, Cynthia; Lévesque, Catherine; Bédard, Dominique; Frouni, Imane; Yesuf, Jemal M; Hamadjida, Adjia; Lévesque, Daniel; Clarke, Paul BS; Huot, Philippe
Highlights: Mechanism underlying anti-dyskinetic efficacy of 5-HT3 receptor antagonists is unclear. Dyskinetic hemi-parkinsonian rats showed increased 5-HT3 levels in the STN, EP and thalamus. Dyskinesia severity negatively correlated with 5-HT3 levels in the striatum and STN. Changes in 5-HT3 levels in the basal ganglia may modulate l -DOPA induced dyskinesia. Abstract: L-3, 4-dihydroxyphenylalanine (l -DOPA) is the mainstay treatment for Parkinson's disease, but its effectiveness during early disease is marred by the eventual development of l -DOPA induced dyskinesia. In hemi-parkinsonian rats, the serotonin type 3 (5-HT3 ) antagonists ondansetron and granisetron alleviated dyskinesia induced by l -DOPA without impeding its anti-parkinsonian action; in parkinsonian marmosets, ondansetron alleviated dyskinesia and enhanced l -DOPA anti-parkinsonian action. Here, we sought to gain insight into the mechanisms governing the anti-dyskinetic action of 5-HT3 antagonists and measured 5-HT3 receptor levels across different brain, using [ 3 H]GR65630 autoradiographic binding. Brain sections were chosen from 6-hydroxydopamine (6-OHDA)-lesioned rats exhibiting abnormal involuntary movements (AIMs), as well as l -DOPA-naïve 6−OHDA and sham-lesioned animals. [ 3 H]GR65630 binding increased in the ipsilateral subthalamic nucleus of 6-OHDA-lesioned rats with mild and severe AIMs, (3-fold changes, P < 0.001). [ 3 H]GR65630 binding also increased in the ipsilateral entopeduncular nucleus and thalamus of 6-OHDA-lesioned rats with severe AIMs (75 % and 88 %, P < 0.05). AIMs scores negatively correlated with [ 3 H]GR65630 binding in the ipsilateral dorsolateral striatum and contralateral subthalamic nucleus ( P < 0.05). These results suggest that alterations in 5-HT3 mediated neurotransmission may contribute to the pathophysiology of l -DOPA induced dyskinesia.